Florence text: Pro et contra - Вальченко, Инна Викторовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
This article explores problem of florence text existence as a type of a local test, considering different points of view of literature professionals. The following article presents text material, that illustrates consistent interest of the russian authors to Florence. Provided examples allow us to assert that florence text has already being well formed in russian literature, has it's specifics and is an interesting object for the further investigation.